Midazolam for Conscious Sedation During Endoscopy: Cheaper and Safer Alternative for Resource-poor Settings (Journal of Shaheed Suhrawardy Medical College, 2022)
Upper gastrointestinal endoscopy is usually carried out using conscious sedation or general anesthesia all over the world. However, due to resource-poor conditions in countries like Bangladesh, physicians have to use topical anesthesia, which eventually leads to a painful and fearful endoscopic experience for most of the patients here. To improve this situation, a crosssectional study was carried out in a tertiary medical center near Dhaka, Bangladesh from March 2013 to October 2018. A total of 4557 patients were included in this study. Among them, 2236 patients were sedated with low dose Midazolam in a conscious sedation procedure, while 2321 patients underwent endoscopy with only topical anesthesia using Lidocaine gel and Lidocaine spray. It was found out that patient satisfaction with Midazolam was 99% compared to only 10% with lidocaine use. Besides, only 4% of patients were restless, but did not need anesthetic support, when Midazolam was used. In contrast, 35% of patients with topical anesthesia were found restless and were assisted. Midazolam is certainly a better and cheaper alternative in resource-poor settings and provides a painless, patient-friendly endoscopic experience without the need for anesthetic support.J Shaheed Suhrawardy Med Coll 2021; 13(1): 33-35